A case of general paralysis of insanity - Shetty, Prathibha S (Journal of All India Institute of Speech and Hearing, 1970)
Mr R., aged 39 years came to the All India Institute of Speech and Hearing on 6-12-1968 with a complaint that his speech was not clear and was difficult to understand. The speech pathologist’s observation was that in running speech articulation was severely distorted. Articulation in words however was much better. Sounds ’r’ ’s’ ’t’ ’d’ ’ ’ ’ and ’sh’ (S) were found to be severely dis- torted. His control over the tongue seemed to be disturbed and he could not raise his tongue in running speech. However, under control, with stimulation he could say all the sounds correctly. He was also observed to continuously smack his lips and clutter his words while speaking. The case was tested for aphasia and the results were negative. E.N.T. findings as well as hearing were found to be normal